Employees’ Attitude as a Determinant of Talent Management-A Study on Indian Public and Private Sector Industries - Rasmita Behera, Prof (Dr.) A.K. Das Mohapatra (International Journal of Advanced Science and Technology, 2020)
Over the past few decades, talent management has gained prominence in the field of human resource management all over the world. Talented people are often seen to be leaving their organizationsfor not having the prospect of growth,coupled with factorslike improper utilization of their skills and knowledge. Therefore, organizations the worldwideface a bigger challenge how to manage and develop their human resources to their competitive advantage and also to retain them on a long term basis. This paperexamines theemployees’ attitudetowards talent management, and their contributions towards the organizations’ growth. The study is based on primary data collected through structured questionnaire from the employees of five kinds of organizations such as banking, manufacturing, power and energy, IT and pharmaceutical companies in India. The collected data has been analysed through descriptive statistics, ANOVA and F-Test, besides mean, standard deviations and test of homogeneity. The study indicates that the attitude of employees does have a significant effect on talent management, and that there exists a significant difference in the attitude of employees of private sector firms than those of the public sector firms on talent management.